2007
DOI: 10.2337/dc06-2008
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Breastfeeding on Obesity and Type 2 Diabetes Risk Factors in Latino Youth With a Family History of Type 2 Diabetes

Abstract: OBJECTIVE -To determine whether breastfeeding is related to total adiposity, regional adiposity, and glucose and insulin dynamics in overweight Latino youth throughout puberty. RESEARCH DESIGN AND METHODS -The relation between breastfeeding and diabetes risk was determined in 240 overweight (BMI Ն85th percentile) Latino children (aged 8 -13 years) with a positive family history of type 2 diabetes. Children were examined at baseline (Tanner pubertal stage 1) and for 2 more years as they advanced in pubertal mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
2
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 36 publications
3
21
2
1
Order By: Relevance
“…Precisely, through inflammatory factors (e.g., interleukin (IL)-6 and TNF-alpha), also found in human breast-milk, 63,64 these hormonal molecules influence fat and lean body mass development in healthy term infants, 63,64 and enhance appetite signalling, 25 promoting child satiety-responsiveness and decreasing over-eating risk. 65 …”
Section: Breast-feeding and Obesity: Possible Mechanisms Involvedmentioning
confidence: 97%
“…Precisely, through inflammatory factors (e.g., interleukin (IL)-6 and TNF-alpha), also found in human breast-milk, 63,64 these hormonal molecules influence fat and lean body mass development in healthy term infants, 63,64 and enhance appetite signalling, 25 promoting child satiety-responsiveness and decreasing over-eating risk. 65 …”
Section: Breast-feeding and Obesity: Possible Mechanisms Involvedmentioning
confidence: 97%
“…While this study showed that waist circumference has useful predictive qualities, most of the data were derived from studies of obese children across a wide range of ages. Recently, Shaibi et al 28 and Davis et al 29 added substantially to the world MRI database with children.…”
Section: Introductionmentioning
confidence: 99%
“…Because CHWs share culture, language, and knowledge of the community, they engage minority populations more effectively than the formal health care system can. 11,12 Living and working in the same community as the people they serve, CHWs are able to provide individualized attention, focus on behavior-related tasks, and deliver regular feedback on the completion of those tasks. 13 These qualities should lead to improved diabetes self-management and clinical outcomes.…”
mentioning
confidence: 99%